A Study of Integer Partitions and their Derivations - Teklemariam, Netsanet (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This M.Sc. thesis studies the partitions of integers, mainly restricted integers and how to derive them methodically. Analysis is made of different theories of calculating integers which are generating functions, Euler’s identity, McMahon’s recurrence, Sylvester’s approach, Frobenius partitions and generalized partitions. Chapter 1 shows how to obtain partition identities using Ferrer’s diagram, Durfee square and Jacobi’s triple product identity. The basic generation of partition of integers is considered first. This is followed by the expression of partitions using Ferrer’s diagram in chapter 2. In chapter 3, the number of partitions in a set of integers is calculated using the method of function generation. Using the preceding chapters, partition identities are obtained and further explained them in chapter 5 using Durfee squares and its relation to Ferrer’s diagram. Euler’s identity is proven combinatorically by means of bijection in chapter 6 and Euler’s pentagonal number is used to represent a special case of Jacobi’s triple product identity in chapter 7. When the pattern of a pentagonal number is notable, McMahon’s approach is used to generate functions to calculate partitions in restricted integers as discussed in chapter 8. The first Sylvester wave is defined which is an explicit formula for the polynomial part of a restricted partition function. The last three chapters looks at special cases in generalized partitions and use Euler’s result for identically distributed partitions.

ÖZ: Bu tez, tamsayıların, özellikle kısıtlı tamsayıların bölümlerini ve bunların metodik olarak nasıl türetileceğini inceler. Analiz, üreten fonksiyonlar, Euler'in kanunu, McMahon'un tekrarı, Sylvester'ın yaklaşımı, Frobenius bölümleri ve genelleştirilmiş bölümler gibi tamsayıları hesaplamak için farklı teorilerden yapılmıştır. Bölüm 1, Ferrer diyagramı, Durfee karesi ve Jacobi'nin üçlü ürün kimliği kullanılarak bölüm kimliklerinin nasıl elde edileceğini gösterir. İlk önce tamsayıların bölünmesinin temel nesli düşünülür. Bunu, bölüm 2'deki Ferrer diyagramını kullanarak bölümlerin ifadesi takip eder. Bölüm 3'te, bir tamsayı kümesindeki bölümlerin sayısı, fonksiyon oluşturma yöntemi kullanılarak hesaplanır. Önceki bölümleri kullanarak, bölüm kimlikleri elde edilir ve Bölüm 5'te Durfee kareleri ve bunun Ferrer diyagramıyla ilişkisi kullanılarak daha ayrıntılı olarak açıklanır. Euler'in kanunu, 6. bölümde alıntılama yoluyla kombinatorik olarak kanıtlanmıştır ve Euler'in beşgen sayısı, 7. bölümde Jacobi'nin üçlü ürün kimliğinin özel bir durumunu temsil etmek için kullanılmıştır. Beşgen bir sayının modeli dikkate değer olduğunda, McMahon'un yaklaşımı, 8. bölümde tartışılan kısıtlı tamsayılardaki bölümleri hesaplamak için fonksiyonlar oluşturmak için kullanılır. Kısıtlı bir bölme fonksiyonunun polinom kısmı için açık bir formül olan ilk Sylvester dalgası tanımlanmıştır. Son üç bölüm, genelleştirilmiş bölmelerdeki özel durumlara bakar ve özdeş olarak dağıtılmış bölümler için Euler'in sonucunu kullanır.
Master of Science in Applied Mathematics and Computer Science. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2021. Supervisor: Prof. Dr. Benedek Nagy.
Keywords: Thesis Tez; Mathematics Department; Integers; Generating functions; Restricted integers; Euler’s identity; Euler’s pentagonal number; Ferrer’s diagram; Durfee square; McMahon’s approach; Bijection; Sylvester wave; Generalized partitions; Euler’s result